Effect of inhaled cyclosporin on the rat airway: Histologic and bronchoalveolar lavage assessment - CEYHAN, BERRİN (KARGER, 1998)
Airway inflammation plays a pivotal role in asthma. Over the last 10 years, evidence has accumulated for the potential role of lymphocytes in airway inflammation. Since cyclosporin A (Cyc-A) can profoundly influence lymphocyte activation, it is appropriate to consider this drug as a novel antiasthmatic. The effect of inhalation of low doses of Cyc-A on airway inflammation remains unclear. The purpose of this study was to investigate the bronchoalveolar lavage (BAL), peripheral blood cell profiles, and lung biopsy specimens in Cyc-A-pretreated rats. Twenty-nine rats (8 controls, 10 ovalbumin sensitized, and 11 Cyc-A inhaling and ovalbumin sensitized) were included in the study. A commercial intravenous Cyc-A solution was given as a single dose of 20 mg/kg 1 h prior to inhalation of ovalbumin via nebulizer. The total number of BAL cells significantly increased in rats inhaling Cyc-A when compared with ovalbumin-sensitized rats (2.37 +/- 2.34 x 10(6)/ml and 1.01 +/- 0.49 x 10(6)/ml respectively, p < 0.05). There was a significant increase in the percentage of lymphocytes (14.5 +/- 8.5 versus 27.4 +/- 7.4%, p < 0.03), a nonsignificant increase in the percentage of eosinophils (0.8 +/- 1.0 versus 3.0 +/- 4.6%), and a significant decrease in the percentage of polymorphonuclear leukocytes (9.4 +/- 6.9 versus 3.4 +/- 3.8%, p < 0.01) and macrophages (75.4 +/- 5.1 versus 50.2 +/- 11.8%, p < 0.02) in BAL in the ovalbumin-sensitized group as compared with controls. Differential cell counts revealed a higher percentage of neutrophils and macrophages in the BAL of Cyc-A-pretreated rats than in that of the ovalbumin-sensitized group (26.3 +/- 26.8 versus 3.4 +/- 3.8%, p < 0.01 and 66.1 +/- 7.7 versus 50.2 +/- 11.8%, p < 0.02). There was a nonsignificant decrease of lymphocytes and eosinophils in the Cyc-A-pretreated group when compared with the ovalbumin-sensitized group (27.4 +/- 7.4 versus 21.1 +/- 12.4 and 3.0 +/- 4.6% versus 2.4 +/- 2.6%). The peripheral blood total white blood cell count decreased in the ovalbumin-sensitized and Cyc-A-pretreated groups as compared with the control group (2,520 +/- 1,098/mm(3), 3,591 +/- 2,251/mm(3), and 5,975 +/- 2,787/mm(3), respectively, p < 0.01). Tn addition, peripheral eosinophilia was detected in the Cyc-A-pretreated group when compared with controls and the ovalbumin-sensitized group (6.9 +/- 4.7, 2.4 +/- 1.1, and 2.6 +/- 2.4%, respectively, p < 0.01). Light-microscopic examination of the airways revealed prominent eosinophilia in tracheal, bronchial, and bronchiolar sections in the ovalbumin-sensitized group: counts were 1.8 +/- 2.3/HPF, 10.3 +/- 11.4/HPF, 63.3 +/- 45.0/HPF, respectively. Cyc-A resulted in a decrease of the eosinophil counts/HPF to O/HPF in trachea (p < 0.05), to 4.3 +/- 9.4/HPF in bronchi (p < 0.02), to 19.4 +/- 38.4 in bronchioles (p < 0.004). In conclusion, the present study supports the theory that locally administered inhaled low-dose Cyc-A is effective on inflammatory cells of sensitized airways and peripheral cells. It may therefore be useful in elucidating the inflammatory mechanisms involved in asthma.
Keywords: cyclosporin A; bronchoalveolar lavage; airway inflammation; rats; PLATELET-ACTIVATING-FACTOR; BROWN-NORWAY RATS; BRONCHIAL HYPERRESPONSIVENESS; EOSINOPHIL INFILTRATION; LYMPHOCYTES-T; GUINEA-PIG; CELL RESPONSES; SEVERE ASTHMA; ANTIGEN; LUNG